Oral benzo[a]pyrene in Cyp1a1/1b1(–/–) double‐knockout mice: Microarray analysis during squamous cell carcinoma formation in preputial gland duct1. Issue 9 (4th December 2012) - Gálvez‐Peralta, Marina; Shi, Zhanquan; Chen, Jing; Miller, Marian L.; Nebert, Daniel W.
Abstract: Benzo[ a ]pyrene (BaP) is a prototypical polycyclic aromatic hydrocarbon (PAH) found in combustion processes. Cytochrome P450 1A1 and 1B1 enzymes (CYP1A1, CYP1B1) and other enzymes can activate PAHs to reactive oxygenated intermediates involved in mutagenesis and tumor initiation; also, CYP1 enzymes can detoxify PAHs. Cyp1 (+/+) wild‐type (WT) and Cyp1b1 (–/–) knockout mice receiving oral BaP (12.5 mg/kg/day) remain healthy for >12 months. In contrast, we found that global knockout of the Cyp1a1 gene (1a1KO) results in proximal small intestine (PSI) adenocarcinoma within 8–12 weeks on this BaP regimen; striking compensatory increases in PSI CYP1B1 likely participate in initiation of adenocarcinoma in 1a1KO mice. Cyp1a1/1b1 (–/–) double‐knockout (DKO) mice on this BaP regimen show no PSI adenocarcinoma, but instead preputial gland duct (PGD) squamous cell carcinoma (SCC) occurs by 12 weeks. Herein, we compare microarray expression of PGD genes in WT, 1a1KO and DKO mice at 0, 4, 8, 12 and 16 weeks of oral BaP; about four dozen genes up‐ or down‐regulated during most critical time‐points were further verified by qRT‐PCR. In DKO mice, CYP3A59 was unequivocally identified as the BaP‐inducible and BaP‐metabolizing best candidate responsible for initiation of BaP‐induced SCC. Striking increases or decreases were found in 26 cancer‐related genes plus eight Serpin genes in DKO, but not in 1a1KO or WT, mice on this BaP regimen; of the 26, 8 were RAS‐related oncogenes. The mechanism by which cancer‐related genes are responsible for SCC tumor progression in the PGD remains to be elucidated. Abstract : What's new? Polycyclic aromatic hydrocarbons such as BaP, present in cigarette smoke, among other places, are known to cause cancer. This study investigated the up‐ and down‐regulation of various genes in response to oral BaP exposure in mice. The authors particularly looked at two enzymes, Cytochrome P450 1A1 and 1B1. Mice with both enzymes, and those missing 1B1, resist cancer when exposed to BaP, but mice lacking both CYP1A1 and CYP1B1 soon develop tumors of the preputial gland duct. What other genes are involved? Using microarray analysis, the authors identified a couple of dozen cancer‐related genes that showed striking increases or decreases in expression with BaP treatment in the absence of Cyp1A1 and Cyp1B1. The gene encoding CYP3A59 emerged as the strongest candidate for cancer initiation.